Menggali Peran Pendamping Sosial dalam Mendorong Kemandirian Ekonomi KPM PKH: Studi Kasus di Kelurahan Kebon Jayanti Kota Bandung - Faustina, Bernadette; Susilowati, Ellya; Gaol, Harapan Lumban (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2024)
The Family Hope Program (PKH) aims to improve the welfare of poor families through cash assistance with certain conditions. However, the success of this program doesn’t depend on the financial aid itself, but also on the role of social facilitator in empowering the beneficiary families to be economically independent. This study aims to obtain an overview of the role of social facilitator in building the economic independence of the beneficiary Family Hope Program in Kebon Jayanti Village which consists of facilitation, education, representation, and technical roles. This research uses a descriptive qualitative method. Data was collected using purposive sampling so that 13 informants were netted from the person in charge of PKH, Kebon Jayanti Village officials, PKH external parties, and the beneficiary family of PKH. The source of the data came from primary and secondary data with data collection techniques through interviews, observation, and documentation studies. This research found that there are obstacles in the implementation of assistance, namely the absence of resource mapping and the lack of access of social facilitator to networks in Bandung City that can be utilized by KPM PKH in building economic independence.